Narrating oneself and “putting in common”: life history and proximity communication (Intercom - Brazilian Journal of Communication Sciences, 2023)
This paper reflects the life history method, from a proximity communication approach, further elaborated in-depth as a theoretical-methodological frame of reference in the thesis “Proximity and confessions: experiences in homelessness and building of oneself. Life histories and resistance in Historic Downtown Salvador, Bahia”. At the interception of these paradoxical methodological frameworks, the aspects of “the meeting of worlds” and “the truth of the other” were highlighted, thus enabling an assessment of the role assigned to sensitivity, respect for the other and the fair extent to which one places oneself, while also valuing the dialogic contexts between narrators and the researcher embodied in qualitative research.
Keywords: Life history; Proximity communication; Intersubjectivity; Homeless subjects; Historic Downtown Salvador